Comparison of the Prehospital Trauma Life Support recommendations and the German national guideline on treatment of patients with severe and multiple injuries - Häske, David; Münzberg, Matthias (The journal of trauma and acute care surgery, 2016)
BACKGROUND The Prehospital Trauma Life Support (PHTLS) concept is well established throughout the world. The aim is to improve prehospital care for patients with major trauma. In 2011, a German Level 3 (S3) evidence- and consensus-based guideline on the treatment of patients with severe and multiple injuries was published. The scope of this study was the systematic comparison between the educational content of the worldwide PHTLS concept and the German S3 Guideline. METHODS A total of 62 key recommendations of the German S3 Guideline were compared with the content of the English PHTLS manual (eighth edition). Depending on the level of agreement, the recommendations were categorized as (1) agreement, (2) minor variation, or (3) major variation. Comparison was done via a rating system by a number of international experts in the field of out-of-hospital trauma care. The Delphi method was used to get the final statements by indistinct or board-ranged ratings. RESULTS Overall, there was no conformity in 12%. In 68% a total agreement and in 88% conformity with slight differences of minor variations were found between the key recommendations of the guideline and the PHTLS manual. The PHTLS primary assessment has a large conformity for the following individual priorities: airway, 92%; breathing, 92%; circulation, 63%; disability, 100%; exposure, 89%. CONCLUSIONS According to our comparison, the PHTLS manual is largely compatible with the German S3 Guideline from 2011. The 12% divergent statements concern mainly fluid resuscitation. Minor deviations in the prehospital care are due to a national guideline with an emergency medical service with emergency physicians (S3 Guideline) and a global PHTLS concept.